Analysis of rural infrastructure development using village funds in Bagan Nibung Village (Fakultas Ekonomi Universitas Kadiri, 2022)
This study aims to analyze the development of village funds for infrastructure development and the best hamlets in Bagan Nibung Village, Simpang Kanan District, Rokan Hilir Regency. The indicators of development in the hamlet are human resources, economy, and infrastructure. The sampling method is a purposive method for as many as 57 people. This study uses a descriptive method to see the development of village funds and the AHP and Borda methods to see the ranking of development between hamlets. The most significant village revenue comes from transfer receipts, while other revenues are minimal. In the village expenditure structure, the components of significant expenditure are expenditures for government and development. Spending on hamlet infrastructure activities was mostly in Pematang Lada, Inti Raya, and the least in Suka Makmur. The process hierarchy analysis results show the highest HR variable in the Inti Raya Hamlet. The results of the highest regional economic variable AHP in Suka Makmur. The AHP results show that the infrastructure variable has the highest in Pematang Lada. Borda's analysis results show that the hamlets with the best development ranking are Pematang Lada, Inti Raya, and Suka Makmur.